Pelayanan Publik dan Keterbukaan Informasi Publik Berbasis Pendidikan Masyarakat dalam Praktek Tata Kelola Desa Pengabdian Masyarakat di Desa Sindangheula - Oktavianus Abrianta Sembiring; H.R. Jazuli; Ahmad Lanang Citrawan; Annisa Indah Nuari (LPPI UMN AL WASHLIYAH, 2026)
Public service delivery and public information disclosure constitute essential components of governance grounded in the principles of good governance, particularly at the village government level as the foremost service unit that directly interacts with the community. In practice, the implementation of village public services continues to encounter various challenges, including the limited understanding of village officials regarding public service standards and public information disclosure mechanisms, as well as the low level of community participation in accessing and overseeing village services. These conditions have resulted in the suboptimal realization of transparent and accountable village governance. This community service activity aims to describe and analyze the strengthening of public service delivery and public information disclosure based on community education within the governance practices of Sindangheula Village, Serang Regency. The approach employed is normative–empirical, conducted through the examination of statutory regulations in the fields of public services and public information disclosure, alongside the mapping of the empirical conditions of village public services through educational activities, participatory discussions, and mentoring for both village officials and the community. The results of this community service activity indicate an improvement in the understanding of both village officials and the community regarding their rights and obligations in public service delivery, the importance of public information disclosure, and its relation to the principles of transparency and accountability in village governance. Furthermore, the community education initiatives implemented have strengthened the awareness of village officials in consistently applying the principles of good governance in daily public service practices.